Characterisation of ionospheric TEC variations over the equatorial and polar regions during solar cycle 24 - Mohd Hamzah, Siti Zainab (2018)
The TEC variations in the equatorial and polar region are known to be high compared to the mid latitude region. Investigation on ionospheric TEC at individual regions has been carried out by many studies but the investigation between these regions simultaneously is still lacking. TEC values from Libreville (NKLG), Gabon (0.4162°N, 9.4673°E), and Ny-Alesund (NYA1), Norway (78.9235°N, 11.9099°E), each representing equatorial and polar station, respectively, are obtained for the year 2009, 2011, and 2013 to observe their TEC behaviors. The diurnal and seasonal variations of TEC and geomagnetic effects on TEC variations are analyzed for both stations. Besides, the rate of TEC change, K, is obtained to relate the TEC variations between these locations simultaneously. The pseudo-TEC measurement measured by dual frequency GPS which can be obtained from IGS server, is used to calculate vertical TEC. The ranges of maximum diurnal TEC at NKLG and NYA1 station is 23-114 TECU and 8-55 TECU, respectively. The seasonal TEC peak at both stations encountered the highest TEC at equinoctial months and the lowest value at solstitial months. However, in 2009, the seasonal TEC showed the highest and lowest TEC peak, both at equinoctial months at NYA1 station. During geomagnetic days, the enhancement percentages of TEC are found on 22 July 2009 and 17 March 2013 at NKLG station, and 22 July 2009 and 25 October 2011 at NYA1 station. The decrement percentage of TEC observed on 25 October 2011 and 17 March 2013 at NKLG and NYA1 station, respectively. The rate of TEC change shows a same definite pattern over all the years. It can be concluded that the hourly maximum TEC values at NKLG station fell within 0.4-1.9 times larger than that NYA1 station. This study helps to have more understanding of the unique characteristics at the equatorial and polar ionosphere.